2014
DOI: 10.1111/nph.12920
|View full text |Cite
|
Sign up to set email alerts
|

A novel Arabidopsis CHITIN ELICITOR RECEPTOR KINASE 1 (CERK1) mutant with enhanced pathogen‐induced cell death and altered receptor processing

Abstract: SummaryPlants detect pathogens by sensing microbe-associated molecular patterns (MAMPs) through pattern recognition receptors. Pattern recognition receptor complexes also have roles in cell death control, but the underlying mechanisms are poorly understood. Here, we report isolation of cerk1-4, a novel mutant allele of the Arabidopsis chitin receptor CERK1 with enhanced defense responses.We identified cerk1-4 in a forward genetic screen with barley powdery mildew and consequently characterized it by pathogen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 61 publications
4
91
0
Order By: Relevance
“…The epidermal growth factor receptor is modified at the transmembrane domain to release an active intracellular domain: the latter is translocated to the nucleus, where it may regulate gene expression (Carpenter and Liao, 2013). In plants, cleavage at the ectodomain has been proposed for several RLKs, like the rice PRR Xa21, the Arabidopsis regulator CHITIN ELICITOR RECEPTOR KINASE1, and the symbiotic receptor kinase from Lotus japonicus (Park and Ronald, 2012;Antolín-Llovera et al, 2014;Petutschnig et al, 2014). However, the biological significance of these observations needs to be further shown experimentally.…”
Section: The Bak1 Ectodomain Influences Regulatory Processes In Plantmentioning
confidence: 99%
“…The epidermal growth factor receptor is modified at the transmembrane domain to release an active intracellular domain: the latter is translocated to the nucleus, where it may regulate gene expression (Carpenter and Liao, 2013). In plants, cleavage at the ectodomain has been proposed for several RLKs, like the rice PRR Xa21, the Arabidopsis regulator CHITIN ELICITOR RECEPTOR KINASE1, and the symbiotic receptor kinase from Lotus japonicus (Park and Ronald, 2012;Antolín-Llovera et al, 2014;Petutschnig et al, 2014). However, the biological significance of these observations needs to be further shown experimentally.…”
Section: The Bak1 Ectodomain Influences Regulatory Processes In Plantmentioning
confidence: 99%
“…14 Interestingly, cerk1-4 plants lack a soluble CERK1 ectodomain fragment that is released into the apoplast of wild-type plants by an N-terminal shedding process, suggesting that breakdown products of the ectodomain shed from the CERK1-4 receptor variant cause the mutant phenotype. 14 To test, whether the nucleoporin MOS7/NUP88 is required for manifestation of cerk1-4 associated phenotypes, we generated the cerk1-4 mos7-1 double mutant and analyzed its growth morphology and cell death response upon inoculation with Bgh. We found that mos7-1 (in ecotype Col-0) fully suppresses the stunted rosette growth of cerk1-4 (in ecotype Col-3 gl1) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…14 Both, the Bgh-induced cell death response and growth retardation of cerk1-4 at old age are independent of chitin signaling, yet require accumulation of the defense hormone SA and an intact SA signaling pathway, since cerk1-4 plants deficient in the SA biosynthetic enzyme SID2 or the downstream SA regulators EDS1 and PAD4 resemble Col-3 gl1 wild-type plants. 14 Interestingly, cerk1-4 plants lack a soluble CERK1 ectodomain fragment that is released into the apoplast of wild-type plants by an N-terminal shedding process, suggesting that breakdown products of the ectodomain shed from the CERK1-4 receptor variant cause the mutant phenotype. 14 To test, whether the nucleoporin MOS7/NUP88 is required for manifestation of cerk1-4 associated phenotypes, we generated the cerk1-4 mos7-1 double mutant and analyzed its growth morphology and cell death response upon inoculation with Bgh.…”
mentioning
confidence: 99%
See 2 more Smart Citations